The Double Fock Space of Type B - Bożejko, Marek; Ejsmont, Wiktor (Symmetry, Integrability and Geometry: Methods and Applications, 2023)
In this article, we introduce the notion of a double Fock space of type B. We will show that this new construction is compatible with the combinatorics of counting positive and negative inversions on a hyperoctahedral group.